Existentialism in the Mathnawi Mem u Zin - Rashid, Jihad (Humanities Journal of University of Zakho, 2020)
Existentialism is one of the philosophical schools of thoughts that can be analyzed in the light of the thoughts and affirmations of poets. This research tries to demonstrate the basic principles of existentialism in Mathnawi of Mem and Zin. Literature is associated with philosophy since literature deals with human condition and essential thoughts of human. Mathnawi of Mem and Zin is one of the works that can be understood philosophically, and this indicates Ahmad Khani's greatness undoubtedly .The aim of this research is understanding and being familiar with existentialism in Mem and Zin, which is one of the divine type, and that it can clarify how views of Khani conforms the basic philosophical principles of this school. In the epic of Mem and Zin, many elements of existentialism can be found such as individuality, faith, freedom, anxiety, rationality and concept of transcendence and the most important one which is finding the spiritual freedom. This research is the library research since it is based on content analysis. The research findings indicate the role and the importance of thoughts and decisions of human in achieving excellence and understanding the concepts of choiceness and freedom, apprehension, communicating and being in contact with others, faith, rationalism and transcendence. The epic of Mem and Zin can be considered as one of the existentialist works because lots of elements of existentialism can be found in the epic. The characters especially the protagonist, themes, and symbols that can be found in this epic are completely existential in color.